Rhythmic ability decline in aging individuals: The role of movement task complexity - Iannarilli Flora; Vannozzi Giuseppe; Minganti Carlo; Capranica Laura; Pesce Caterina (Sciendo, 2022)
Study aim: To investigate age-related changes in rhythmic reproduction ability in relation to the complexity of the adopted movement task.